New Smart Augmented Reality Content to Improve Student Learning Activities in Chinese Language - Sunarti, Sunarti; Bukhori, Herri Akhmad; Widyatmoko, Tiksno; Putri, Amira Eza Febrian (BRILIANT: Jurnal Riset dan Konseptual, 2022)
This study focuses on the development of AR-loaded Listening teaching materials. Based on the results of observations and interviews at the Mandarin language education at Universitas Negeri Malang, it was found that some students felt less interested in the learning model that used printed books provided by the school. In addition, teachers of related subjects also stated that the available learning tools were limited. This research and development use the ADDIE model. Observations and interviews were used to collect the initial data of the study. The sample of the trial subjects of this study were students of the State University of Malang. Research data collection was carried out using questionnaires and observation sheets. Based on the results of field trials, this research and development resulted in a product in the form of digital teaching materials with augmented reality (AR) content which was declared very suitable to be used as teaching materials and could be used in the learning process to foster learning activity with a percentage score of 86.3%.